Советская социология в новейшей историографии (к 50-летию Советской социологической ассоциации) - Городяненко, В. (Социология: теория, методы, маркетинг, 2008)
Sociology of 1950th was the scientific disciplines, initiated not from above, but from below in reply to new realities and challenges of social life. It be came possible under conditions of “thaw” owing to weakening of ideological control, proclamations by N. Khruschev “policy of peaceful coexistance”, and widening of contacts with foreign colleagues. A notice able land mark in the process of institutionalization of sociology in Soviet Union was the establishment of the Soviet Sociological Association (SSA) in 1958 by efforts of P.Fedoseev, V.Nemchinov, A.Rumyantsev, Kh.Suleymanov, M.Kammari et al. The Ukrainian affiliated branch of SSA has been created with the active participation of such well known domestic scientists, as L.Sokhan’, I.Popova, E.Yakuba, V.Chernovolenko, L.Olesnievich et al. Besides co-ordination of scientific activity of sociologists, the SSA had to execute the mere propagandist and censorial functions. How ever we must n’t for get about its contribution to becoming and development of sociology as scientific discipline within the frame work of the USSR.